2010
DOI: 10.1039/b915484a
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and affinity between a fluorinated perylene diimide dye and an alkyl-substituted hexa-peri-hexabenzocoronene

Abstract: Fluorination of alkyl groups is a known strategy for hindering miscibility, thus promoting phase separation, when blends are prepared with a hydrocarbon compound. A new perylene bis(dicarboximide) derivative functionalized with branched N-perfluoroalkyl moieties (BPF-PDI) has been synthesized as electron acceptor to be potentially used in conjunction with the electron donor hexakis(dodecyl)hexabenzocoronene (HBC-C 12 ) in bulk heterojunction solar cells. Aiming at controlling self-assembly between the two comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 94 publications
1
17
1
Order By: Relevance
“…Similar results were obtained with G‐PDI−H and G‐PDI−Cl in CHCl 3 dispersions. Optical absorption spectra of the G‐PDI−PVC multilayers showed the spectral signature of both graphene and PDI, similarly to those observed in dispersion (Figure S5, Supporting Information), with no significant shift in absorption …”
Section: Resultssupporting
confidence: 59%
“…Similar results were obtained with G‐PDI−H and G‐PDI−Cl in CHCl 3 dispersions. Optical absorption spectra of the G‐PDI−PVC multilayers showed the spectral signature of both graphene and PDI, similarly to those observed in dispersion (Figure S5, Supporting Information), with no significant shift in absorption …”
Section: Resultssupporting
confidence: 59%
“…This method would imply a tuning of the chemical properties of D and A molecules, which are complementary from the electronic point of view, so that the SVA step could selectively anneal only one blend component by favoring homomolecular aggregation. Therefore, a new PDI derivative functionalized with branched N ‐perfluoroalkyl moieties ( 16 ) has been synthesized to be blended with the electron donor hexadodecyl substituted HBC ( 1) (Figure 1a) 44. Unexpectedly, the two components interact very strongly in solution already, leading to a supramolecular dimer with a K ass = 10 4 M −1 .…”
mentioning
confidence: 99%
“…h–j) 2D WAXS patterns for extruded samples of BPF‐PDI, HBC‐C 12 , and their 1:1 blend, respectively; dashed circles indicating characteristic reflections of the pure compounds related to intracolumnar packing of the molecules. b–j) Reproduced with permission 44. Copyright 2010, Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…It has been reported that the donor-acceptor complex of PDI can form needle-like nanostructure through attractive intermolecular hydrophobic interactions and the stacking of the aromatic core. 42 As for PASP/3a, a rod-like nanostructure can be observed with an average diameter of about 40-75 nm, and the average length of about 170-400 nm ( Fig. 7e and f).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 89%